2016
DOI: 10.1002/hep.28817
|View full text |Cite
|
Sign up to set email alerts
|

The cystic fibrosis transmembrane conductance regulator controls biliary epithelial inflammation and permeability by regulating Src tyrosine kinase activity

Abstract: In the liver, CFTR regulates bile secretion and other functions at the apical membrane of biliary epithelial cells (i.e cholangiocytes). CF-related liver disease (CFLD) is a major cause of death in patients with CF. CFTR dysfunction affects innate immune pathways, generating a para-inflammatory status in the liver, and other epithelia. This study investigates the mechanisms linking CFTR to TLR4 activity. We found that CFTR is associated in a multi-protein complex at the apical membrane of normal mouse cholangi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 51 publications
(133 reference statements)
6
73
2
1
Order By: Relevance
“…LPS [75,77]. In addition, aberrant activation of Src decreases the epithelia barrier function by destabilizing cell junctional complexes [77,78]. …”
Section: Genetic Mouse Models Of Cholangiocyte Dysfunctionmentioning
confidence: 99%
“…LPS [75,77]. In addition, aberrant activation of Src decreases the epithelia barrier function by destabilizing cell junctional complexes [77,78]. …”
Section: Genetic Mouse Models Of Cholangiocyte Dysfunctionmentioning
confidence: 99%
“…Likewise, it has been reported that intestinal permeability was abnormal in virtually all (i.e., 96%) CF subjects . Acting as a hub, CFTR also stabilizes the apical junction complex through actin‐dependent interactions in epithelial cells so that the loss of apical protein networks orchestrated by CFTR has emerged as a common mechanism of increased permeability in CF epithelia, including gut and bile ducts . A disruption of tight junctions that could explain increased permeability has thus been demonstrated in the small intestine of CF mice …”
Section: Discussionmentioning
confidence: 96%
“…In addition to its channel function, CFTR was also recently shown to operate as a hub for cytoskeletal elements, transmembrane proteins, and signaling molecules . In cholangiocytes, CFTR promotes the assembly of a protein complex that maintains the tyrosine kinase Rous sarcoma oncogene cellular homolog (Src) in an inactive state . Thus, in the absence of CFTR at the apical membrane, this complex does not assemble, resulting in the self‐activation of Src and subsequent increase in TLR4 and NF‐B signaling in response to endotoxins .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, BEC can be more purified but cannot proliferate in culture. Recently, it has been shown that primary cultures of mouse cholangiocytes could be cultured on rat tail collagen for several passages [81] and used for specific functional studies with transgenic mice [82].…”
Section: Cellular Models In Biliary Researchmentioning
confidence: 99%